Inovasi dan Digitalisasi UMKM Menuju Masyarakat Mandiri Desa Penggalian Kec. Tebing Syabandar Kab. Serdang Bedagai - Arseto, Dedy Dwi; Siregar, Aisyah; Damanik, Ayu Zurlaini; Azman, Muhammad Richie; Sari, Gansar Mayang (STIE Bina Karya, 2025)
Problems faced by business actors in Penggalian Village in developing MSMEs. The object of this socialization activity is MSMEs in Penggalian Village. This socialization activity aims to increase efforts to develop MSMEs. Based on the results of observations, it is known that Penggalian Village generally describes that there is a lot of potential, but it has not been explored and optimized in its utilization. The problems in developing MSMEs in Penggalian Village are: lack of knowledge of MSME owners regarding the latest technology. To overcome these problems, it is necessary to conduct socialization regarding what is needed by MSME actors to transform their businesses into digital ones. This activity is carried out in order to encourage the growth of MSMEs in Penggalian Village. In addition, this activity also aims to digitize MSME products in rural areas in order to transform conventional marketing processes into digital ones.